INVESTIGATING CAUSES OF CULTURE SHOCK EXPERIENCED BY INTERNATIONAL STUDENTS - Widya Pramesti; Nurhaeni Nurhaeni; Nurul Imansari (LET: Linguistics, Literature and English Teaching Journal, 2022)
This study aims to investigate the causes of culture shock experienced by international students of Indonesia who study abroad as well as how is the culture shock and how to cope with it. This study employed qualitative research. The research subjects comprised ten international students who study in three different countries; eight in China, one in Australia and one in Netherland. They were selected utilizing purposive sampling techniques and collected through a semi-structured interview. The results of this research showed there are three main conditions of culture shock experienced by international students, that categorized in three dimension of culture shock; affect, behaviour and cognitions. Moreover, it was found that there were several causes of culture shock revealed in academic and non-academic settings. The causes of culture shock in academic settings indicated affecting students GPA score, like language barriers and learning process. While in non-academic settings the culture shock experienced by the international students cause by food, seasons and weather, payment system and people behavior in their host country. Also, the subjects showed the way to cope with culture shock using their own coping strategy and it was revealed that having pre-departure orientation helped students cope with culture shock.